Immediate pelvic defect reconstruction with unilateral gracilis flap in a postoperative patient with vulvar carcinoma - Mendoza, Jose B.; Hernandez, Sandra Y.; Ramírez, Eduardo D.; Lopez, Nohemi; Ugalde, Juan A.; Ríos, Rodolfo L.; Canepa, Patricio; Perrusquia, Daniela (International Journal of Research in Medical Sciences, 2024)
Vulvar cancer is a rare malignancy that primarily affects postmenopausal women. Squamous cell carcinoma is the most common histological type. Clinical presentation can be variable and non-specific, and treatment involves a combination of surgery and radiotherapy. This article presents a clinical case of a 61-year-old patient with squamous cell carcinoma of the vulva, treated with chemotherapy, brachytherapy and radiotherapy, who experienced recurrence. A pelvic exenteration and immediate reconstruction were performed using a unilateral gracilis flap, with satisfactory results. A 2-year follow-up showed no complications.